2016
DOI: 10.4049/jimmunol.1501188
|View full text |Cite
|
Sign up to set email alerts
|

A Brucella spp. Protease Inhibitor Limits Antigen Lysosomal Proteolysis, Increases Cross-Presentation, and Enhances CD8+ T Cell Responses

Abstract: In this study, we demonstrate that the unlipidated (U) outer membrane protein (Omp) 19 from Brucella spp. is a competitive inhibitor of human cathepsin L. U-Omp19 inhibits lysosome cathepsins and APC-derived microsome activity in vitro and partially inhibits lysosomal cathepsin L activity within live APCs. Codelivery of U-Omp19 with the Ag can reduce intracellular Ag digestion and increases Ag half-life in dendritic cells (DCs). U-Omp19 retains the Ag in Lamp-2+ compartments after its internalization and promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…This may also be the case in the HKS model contributing to the induction of a stronger immune response against this antigen. Of note, study of other protease inhibitors has shown that the protease inhibitory activity by itself does not induce immune response against the coadministered antigen; it is the combination of U-Omp19’s immunostimulatory properties together with a delay in antigen degradation that explain the adjuvant properties of U-Omp19 ( 21 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also be the case in the HKS model contributing to the induction of a stronger immune response against this antigen. Of note, study of other protease inhibitors has shown that the protease inhibitory activity by itself does not induce immune response against the coadministered antigen; it is the combination of U-Omp19’s immunostimulatory properties together with a delay in antigen degradation that explain the adjuvant properties of U-Omp19 ( 21 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that it has self-adjuvanting properties ( 20 ) and can also enhance immune responses against the model antigen chicken ovalbumin (OVA) ( 21 , 22 ). The mechanisms responsible for the adjuvant activity of U-Omp19 rely in the inhibition of stomach and gut proteases and recruitment of immune cells to the gastrointestinal mucosa ( 21 ) as well as increased maturation of DCs and enhanced presentation of the antigen by means of delaying antigen digestion at the lysosomes ( 23 ). Thus, mucosal as well as systemic OVA-specific immune responses, Th1, and CD8 + are enhanced if U-Omp19 is codelivered orally.…”
Section: Introductionmentioning
confidence: 99%
“…Viability of cells was more than 95% in all the experiments as measured by trypan blue exclusion test. Mouse bone marrow-derived macrophages (BMM) were generated by differentiation of bone marrow progenitors from C57BL/6 wild type mice, TRIF KO or TLR7 KO mice (provided by Federal University of Minas Gerais, Belo Horizonte, Brazil) with rM-CSF (PeproTech), as previously described [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Viability of cells was >95% in all the experiments as measured by trypan blue exclusion test. Mouse bone marrow‐derived macrophages were generated by differentiation of bone marrow progenitors from C57BL/6 mice with recombinant macrophages colony‐stimulating factor (PeproTech), as previously described 50 …”
Section: Methodsmentioning
confidence: 99%